Quinazolinedione Derivatives as Potential Anticancer Agents Through Apoptosis Induction in MCF-7 - Tanapol Limboonreung; Teetat Suansilpong; Panitan Jumjitvi; Duangporn Lohawittayanan; Sucheewin Krobthong; Sitthivut Charoensutthivarakul (International Journal of Molecular Sciences, 2025)
Breast cancer remains a leading cause of mortality among women worldwide. Surgery, radiation therapy, chemotherapy, and hormone-based treatments are standard therapeutic approaches, but drug resistance and adverse effects necessitate the search for novel anticancer agents. Quinazolinedione derivatives have emerged as potential anticancer compounds due to their cytotoxic and apoptosis-inducing properties. This study aimed to evaluate the apoptotic induction of previously reported quinazolinedione derivatives on MCF-7 breast cancer cells. The cytotoxic effect was assessed using the MTT assay, apoptosis was quantified by Annexin V-PE/7AAD staining and flow cytometry, and apoptosis-related protein expression was analyzed via multiplexed bead-based immunoassays. These findings indicate that two derivatives in the series significantly reduced the cell viability in a dose-dependent manner. Apoptosis was induced primarily through the intrinsic apoptotic pathway as evidenced by the upregulation of caspase-9 and p53 and the downregulation of Bcl-2 and p-Akt. These results highlight quinazolinedione derivatives as promising candidates for breast cancer therapy prompting further investigation into their molecular mechanisms and potential clinical applications.
Keywords: Quinazolinone synthesis and applications; Cancer Mechanisms and Therapy; Cancer-related Molecular Pathways